KARAKTERISTIK BRIKET ARANG DARI CAMPURAN TEMPURUNG KELAPA DAN SERBUK GERGAJI KAYU PALAPI (HERITIERA SP) - Hapid, Abdul; Muthmainnah, Muthmainnah; Ahmad, Ahmad (ForestSains, 2018)
The current high population rate leads to inevitable, greater demand for energy. In fact, most urban communities depend on oil and gas as the energy source for daily usage while the communities in rural and remote areas preferably use woods as fuel. The search for alternative source to reduce the dependency on the availability of fuelwood has been done by utilizing agricultural waste, industrial waste and domestic waste, including coconut shells and sawdust. These wastes can be processed into briquettes as potential solid fuel. The present study aims to investigate the quality of briquettes made from a mixture of coconut shells and palapi sawdust. It was done in May to July 2016 at the Mechanical Engineering Labolatory, Tadulako University. A completely randomized design (CRD) was employed, with three treatments: A (100% coconut shell charcoal), B (85% sawdust + 15% coconut shell charcoal) and C (85% coconut shell charcoal + 15% sawdust). The parameters included density, moisture, volatile matter, ash, and fixed carbon. The results showed the average moisture, ash, fixed carbon, volatile mater, and density of charcoal briquettes were: 4.62?4.99%, 4.51?5.55%, 29.63?53.17%, 36.94?59.88% and 0.48?0.7g/cm3, respectively. It indicates that the mixture of coconut shell and sawdust has a very significant effect on ash content, volatile matter, fixed carbon and density, but insignificant effect on water content.